Improving Understanding in the Development of Teaching Modules in the Independent Curriculum through Training of Mathematics Teacher - Karim Karim; Taufiq Hidayanto; Kamaliyah Kamaliyah; Asdini Sari; Muhammad Rayhan Ramadhan; Muhammad Alif Anwar (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
In implementing the "Independent Curriculum," one of the materials that need to be prepared by the teacher is the teaching module. However, since this is relatively new, the teachers who are members of the Association of Mathematics Teachers of Senior High School in Banjarmasin need to receive training regarding implementing the "Independent Curriculum" and preparing teaching modules. Therefore, a workshop for preparing mathematics teaching modules for mathematics high school teachers needs to be implemented. The purpose of this service is to increase the understanding of high school mathematics teachers in Banjarmasin regarding the "Independent curriculum" and to develop teachers' ability to compose teaching modules. This Community Service Method is implemented using the PAR (Participatory Action Research) approach. The cycles implemented are to know, to understand, to plan, to act, and to change. The results of the service show an increase in understanding regarding the implementation of the “Independent Curriculum” and the participants' ability to develop teaching modules in the “Independent Curriculum”. This is indicated by an increase in the average percentage of teachers answering pre-test to post-test questions correctly from 71.39% to 83.22% and the collection of teaching modules that have been prepared by the participants after completing the workshop and mentoring by the community service team.